Studies on Schismatoglottideae (Araceae) of Borneo LIX : A preliminary conspectus of Schismatoglottis Calyptrata Complex Clade species for Sarawak - Wong, Sin Yeng; Hoe, Yin Chen; Boyce, P.C (International Aroid Society, Inc., 2016)
A preliminary conspectus of species of the Schismatoglottis Calyptrata Complex Clade for Sarawak is presented. Six species are accepted, of which Schismatoglottis baangongensis S.Y. Wong, Y.C. Hoe & P.C. Boyce is newly described, and S. muluensis M. Hotta is resurrected from within S. calyptrata (Roxb.) Zoll. & Moritzi. Current evidence does not support the presence of Schismatoglottis calyptrata sens. strict. in Sarawak, while occurrence on Borneo as a whole is questionable. A modified description of S. calyptrata, excluding characteristics of Bornean taxa hitherto included in synonymy is provided. An identification key to the accepted species for Sarawak is provided, and most are illustrated from living plants.